Recombinant Irisin Ameliorates Insulin Resistance in Type 2 Diabetic Mice - Sana Akram; Hira Zahid; Maimona Tabbsum; Zehra Niazi; Jahanzab Salim; Chaman Nasrullah (Proceedings)
Introduction: An exercise-induced myokine, Irisin, is shown to cause the browning of white adipose tissue, promote glycogen storage, and inhibit glucose and cholesterol formation in the liver. Studies have, however, shown a reduction of circulating irisin in type 2 diabetes, suggesting altered secretion of myokines in the setting of insulin resistance.